Interactive Multimedia Based on Problem-Based Learning for the Natural and Social Sciences (IPAS) Subject for Fourth Grade Elementary School Students - Poniyanti, Ni Nyoman Putri; Agung, Anak Agung Gede; Paramita, Made Vina Arie (MIMBAR PGSD Undiksha, 2024)
The absence of interactive multimedia in learning hinders the achievement of learning objectives. This study aims to analyze the effectiveness of interactive multimedia based on problem-based learning in IPAS lessons for fourth-grade elementary school students. This is a development research study using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The research subjects included experts in instructional design, content, and media, as well as 27 fourth-grade students. Data were collected using questionnaires and tests, and analyzed through descriptive quantitative methods and inferential statistics using a dependent sample t-test. The evaluation results showed that (1) the instructional design scored 92.5% (very good); (2) the feasibility of the interactive multimedia was rated highly feasible by the content expert (92.5%), instructional design expert (95%), media expert (92.5%), individual trial (95%), and small group trial (94.44%); and (3) the effectiveness of the multimedia, based on the dependent sample t-test, yielded a t-value of 9.864 with df = 26 and a significance level of 5% = 1.706, indicating tvalue > ttable, so H0 was rejected and H1 was accepted. Based on these results, it can be concluded that the PBL-based interactive multimedia is both feasible and effective for use in fourth-grade elementary school. The implication of this research is its potential to enhance students’ learning motivation, improve their understanding of the material, and encourage teachers to use innovative learning media to optimally achieve educational goals.